2023
DOI: 10.1186/s41043-023-00349-7
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic: knowledge, attitudes and practices of coronavirus (COVID-19) among patients with type 2 diabetes

Abstract: Background It is necessary to evaluate COVID-19 data on Knowledge, Attitudes and Practices (KAP) to confirm effective protective practice and to reduce risk in society. Hence, the study was carried out to determine KAP towards COVID-19 and the factors associated with knowledge and practices among patients with type 2 diabetes (T2D). Methods In this cross-sectional (descriptive-analytical) study, 357 patients with diabetes in Izeh participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The study by Orok [9] in Nigeria revealed that only 41.2% of participants agreed to be vaccinated, while that by Saied [10] in Egypt revealed that 34.9% of students were vaccinated and 19.4% refused to be vaccinated. The same was true of interns at the CHU in Mali, 66.67% of whom were not vaccinated at the time of the study [11]. In contrast, Kelekar's study [12] in the USA showed that 55% of dental students and 77% of medical students agreed to be vaccinated.…”
Section: Discussionmentioning
confidence: 89%
“…The study by Orok [9] in Nigeria revealed that only 41.2% of participants agreed to be vaccinated, while that by Saied [10] in Egypt revealed that 34.9% of students were vaccinated and 19.4% refused to be vaccinated. The same was true of interns at the CHU in Mali, 66.67% of whom were not vaccinated at the time of the study [11]. In contrast, Kelekar's study [12] in the USA showed that 55% of dental students and 77% of medical students agreed to be vaccinated.…”
Section: Discussionmentioning
confidence: 89%
“…The average age was included in the range of average age between 45 and 58 years old, noted in other studies on the similar topics among diabetics [9] [11] [14] [15]. The female predominance varies according to the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The collected data will be analyzed with Smart PLS. Smart PLS software is suitable for use in processing this research data because the output generated from testing using Smart PLS can make the reader's understanding better [61].…”
Section: Sample and Proceduresmentioning
confidence: 99%